Tropical cyclone sensitivity to ocean coupling in the ECMWF coupled model. Issue 5 (25th May 2017) - Mogensen, Kristian S.; Magnusson, Linus; Bidlot, Jean‐Raymond
Abstract: We present an investigation of the performance of the ECMWF coupled atmosphere‐waves‐ocean model for different ocean and atmosphere resolutions on a series of tropical cyclones in the Western Pacific with the aim to better understand the coupled feedback mechanisms in these extreme conditions. For some of the test cases, we only find little impact of coupling the atmosphere to the ocean, while in others, we observe a very large impact. To further understand these differences, we have selected two tropical cyclones (TCs) as case studies: TC Haiyan (with small impact of coupling) and TC Neoguri (with large impact of coupling). The comparison between these two cases suggests that the upper ocean stratification is the key in determining the strength of the coupled feedback. A strong coupled feedback is found whenever the ocean heat content of the upper layer is low while a very weak coupled feedback is found whenever the ocean has a thick warm mixed layer. The oceanographic response to tropical cyclones for the two storms has been compared to sea surface temperature and derived surface currents from drifting buoys and to subsurface observations from Argo and ship launched XBT's. These comparisons show that we are able to realistically reproduce the atmospheric and oceanographic interaction during tropical cyclone conditions which gives us confidence that the coupled modeling system is physically sound. Key Points: We have used the coupled ECMWF model to simulate a set of tropical cyclones in the North‐western Pacific The impact of coupling the atmosphere to the ocean is different for different TC's We use TC Haiyan and TC Neoguri to illustrate the reasons for the different coupling impact